The 2006 quadrennial defence review: implications for Asian security - Loo, Bernard (2016)
Barely three months after it was released, the impact of the US 2006 Quadrennial Defence Review (QDR) is beginning to be felt. There is now talk of expanding NATO to include non-European partners such as Japan, South Korea and Australia. Japan and the United States have also concluded long-running negotiations concerning the relocation of United States military force currently stationed in Okinawa to the Pacific island of Guam.